MITOLOGI NYANYIAN RAKYAT DALAM TRADISI RITUAL MADDUI MASYARAKAT KARAMPUANG KABUPATEN SINJAI TINJAUAN SEMIOTIKA ROLAND BARTHES - Darwana, Siti; Anshari, Anshari; Faisal, Faisal (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2022)
The purpose of this study was described the meaning of denotation, connotation and myths in folk songs in the Maddui ritual tradition of the Bugis Karampuang community based on Roland Barthe’s theory. This research is descriptive qualitative. Result of the study show, the connotative meaning can be related to the existence of  gods, natural rulers as well as the institutional structure or traditional leadership of Karampuang. The connotative meaning of Maddui poetry is a strategy on dealing with life by maintaining good relations between humans and god as well as relationships between humans and other humans and how humans relate to other nature. The mytology of Maddui poetry delivered ideology againts the existence and gods power.